Risk factors for healthcare-associated Clostridium difficile infection in pediatric hematopoietic stem cell transplant recipients. (4th October 2017) - Drew, Richard H; Ni, Clara; Kelly, Matthew; Wilson, Dustin; Sarubbi, Christina; Steinbach, William
Abstract: Background: Limited published literature exists to identify unique risk factors for Clostridium difficile infection (CDI) in pediatric hematopoietic stem cell transplantation (HSCT) recipients. Our objective was to describe the epidemiology of CDI in pediatric patients undergoing HSCT and to identify potential risk factors for CDI. Methods: This IRB-waived, single-center retrospective review included Duke University Hospital (DUH) patients 12 months of age or older admitted to pediatrics between March 1, 2012 and August 23, 2016 undergoing initial HSCT during the index hospitalization. The primary endpoint (PCR-confirmed CDI within 100 days post-transplantation) was characterized using descriptive statistics. Transplant type, prior CDI history, days of total parenteral nutrition (TPN), and antibiotic use intensity scores were compared between occurrence groups using Pearson's chi-square, Wilcoxon rank-sum or Student's t tests as appropriate. Results: 207 subjects (most Caucasian [55%] and male [61%]) were included, and 15 (7.2%) died. CDI occurred in 24 (12%) within a median (interquartile range) of 35 (9, 47) days since HSCT, and most (92%) were hospital-onset. All cases were healthcare-associated and mild-moderate in severity. None of the patients experienced CDI-related complications. CDI-positive and CDI-negative patients were similar with regards to demographics. Higher median (adjusted) days of TPN (80.6 vs. 29, P < 0.0001) and antibiotic use intensity scores (382.8 vs. 191.0, P < 0.0001), respectively, were associated with CDI. No significant differences between these groups were observed with regard to transplant type ( P = 0.28) and prior CDI history ( P = 0.10). Conclusion: CDI occurred in 12% of pediatric patients within 100 days of undergoing initial HSCT. Onset of this mild-moderate, uncomplicated disease occurred within a median of 35 days and commonly during hospitalization. Patients with CDI were more likely to have increased use of TPN and a higher antibiotic use intensity score. Disclosures: All authors: No reported disclosures.